Radioactivity concentration measurements in fish and shellfish samples from the west coast of Canada after the Fukushima nuclear accident (2011–2018). (October 2022) - Cooke, M.W.; Trudel, M.; Gurney-Smith, H.J.; Kellogg, J.P.; Cullen, J.T.; Francisco, B.B.A.; Mercier, J.F.; Chen, J.
Abstract: Radioactive contamination of the Pacific Ocean following the Fukushima nuclear accident has raised public concern about seafood safety, particularly in coastal Indigenous communities. To address this, Health Canada and partners have collected and analyzed a total of 621 samples of commonly consumed salmon, ground fish, and shellfish from the Canadian west coast from 2011 to 2018. While the vast majority of the 137 Cs and 134 Cs levels were below the Minimum Detectable Concentration (MDC, typically 0.7–1.0 Bq kg −1 fw for a 6 h counting), further examination of 19 fish samples revealed 137 Cs concentrations of 0.17–0.53 Bq kg −1 fw with an average value and uncertainty (k = 1) of 0.29 ± 0.02 Bq kg −1 fw. Of these, only two samples were found to have trace levels of 134 Cs likely derived from the Fukushima accident. The global fallout contribution from atmospheric nuclear weapons testing to the observed 137 Cs in these two samples was determined to be 0.26 ± 0.08 Bq kg −1 fw (49 ± 14%) and 0.12 ± 0.02 Bq kg −1 fw (24 ± 4%) for collection years 2015 and 2016, respectively. The annual average level of 137 Cs in fish and shellfish was also determined by spectral summation for collection years 2014–2018. In fish, 137 Cs levels determined through spectral summation were relatively constant (0.18–0.25 Bq kg −1 fw) with an average value and uncertainty of 0.21 ± 0.02 Bq kg −1 fw. By contrast, 38 shellfish samples (bivalves) were measured and revealed no radiocesium or other anomalies in either tissue or shell. In all, measurements over eight years showed that the radioactivity in fish and shellfish was dominated by natural radionuclides and that the level of anthropogenic radionuclides, as indicated by the radioactive cesium content, remained small. An upper bound for ingested dose from 137 Cs was determined to be approximately 0.26 μSv per year, far below the worldwide average annual effective dose of 2400 μSv from exposure to natural background radiation. We can therefore conclude that fish, such as salmon, ground fish, and shellfish from the Canadian west coast are of no radiological health concern despite the Fukushima Dai-ichi nuclear accident of 2011. Highlights: We screened 621 marine samples from Canada's west coast for radioactivity since the Fukushima accident. Gamma spectral summation employed to derive average 137 Cs content of fish and shellfish. Average activity concentration of 137 Cs in fish ranged from 0.18 to 0.25 Bq kg −1 (fresh weight) between 2014 and 2018. Cesium-134 was identified in two screened fish samples upon further examination. No observed anthropogenic radioactivity in either shells or meat of shellfish. Radioactive content dominated by naturally occurring radionuclides and poses no health risk. .